Seasonal to interannual variability on the southeast Greenland shelf: a study focused on the Sermilik area - Facchinetti, Federica (Università Ca' Foscari Venezia, 2020)
The main objective of this thesis is to analyze the water mass variability and the circulation of the East Greenland boundary current system on the SE continental shelf and to properly represent the shelf/fjord exchange and fjord dynamics. Since the relative partitioning of the water masses composing the East Greenland Coastal Current (EGCC) changes both seasonally and inter-annually, a more complete understanding of this variability is important for (I) evaluating the amount of heat entering the glacial fjords and the melting of Greenland's outlet glaciers and (II) investigating the amount of freshwater the EGCC carry, influencing the stratification of the adjacent Labrador Sea, and in turn the deep convection and the strength of the Atlantic Meridional Overturning Circulation. Regarding the variability and evolution of the East Greenland boundary current system, the eddying GLOB16 configuration (with horizontal resolution of ~4 km in the region of interest) based on NEMO ocean model is used. On the other hand, to investigate the ocean dynamics within a fjord, a frontier-resolution configuration (with horizontal resolution of ~1 km in the region of interest) is employed in order to better resolve the ocean circulation inside the fjord and its interplay with the “open ocean” dynamics. Considering that the bathymetry plays a key role in regulating the AW inflow from the shelf and its circulation within a fjord, a new regional bathymetry product, BedMachine, is used to choose a more accurate input for the High-RES configuration, allowing a robust representation of the 3D fjord geometry and consequently the processes within.